1991
DOI: 10.1111/j.1751-0813.1991.tb03173.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dung from ivermectin‐treated sheep on oogenesis and survival of adult Lucilia cuprina

Abstract: Females of the Australian sheep blowfly, Lucilia cuprina, exploit sheep dung as a source of protein for egg development. Flies fed on dung collected from sheep 1 to 6 days after being drenched with the broad-spectrum antiparasitic drug ivermectin showed delayed reproductive development and reduced fecundity. Male and female survival was also reduced. Despite these effects, except where the recommended frequency of drenching (1 to 4 times per annum) is greatly exceeded, it is unlikely that ivermectin residues w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
4
14
0
Order By: Relevance
“…When protein is scarce, or of poor quality, females either fail to mature any oocytes, or mature fewer than their full complement (Barton Browne et al., 1979; Vogt et al., 1985a). Previous studies on the reproductive biology of L. cuprina have shown that sheep dung was either an inadequate source of protein for ovarian development (Mackerras, 1933; Clift & McDonald, 1976) or, at best, suboptimal (Webber, 1958; Cook, 1991; Mahon & Wardhaugh, 1991). For example, Webber (1958) showed that female flies were able to develop mature oocytes when fed with sheep faeces voided during spring and autumn, but failed to do so when provided with faeces dropped during summer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When protein is scarce, or of poor quality, females either fail to mature any oocytes, or mature fewer than their full complement (Barton Browne et al., 1979; Vogt et al., 1985a). Previous studies on the reproductive biology of L. cuprina have shown that sheep dung was either an inadequate source of protein for ovarian development (Mackerras, 1933; Clift & McDonald, 1976) or, at best, suboptimal (Webber, 1958; Cook, 1991; Mahon & Wardhaugh, 1991). For example, Webber (1958) showed that female flies were able to develop mature oocytes when fed with sheep faeces voided during spring and autumn, but failed to do so when provided with faeces dropped during summer.…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive development of L. cuprina , when fed on sheep faeces collected at different seasons of the year, was sampled at various intervals post‐emergence and compared with that observed among females fed on protein‐rich ovine liver. Flies were obtained from an anautogenous laboratory colony (laboratory strain P) that had been in culture for more than 100 generations (Mahon & Wardhaugh, 1991). The experimental design involved eight feeding regimes (seven of faeces and one of ovine liver), each replicated three times.…”
mentioning
confidence: 99%
“…For example, concentrations in faeces after a therapeutic treatment were sufficient to kill adult dung beetles . Nevertheless, attempts to control parasitic flies by treating them with avermectins so that residues in dung exert a beneficial insecticidal effect have met with little or no success (Mahon & Wardhaugh, 1991;Cook, 1993;Floate et al, 2001;Wardhaugh et al, 2001c).…”
Section: Environmental Effectsmentioning
confidence: 99%
“…The larval development of the house fly Musca domestica and the bush fly Musca vetustissima are significantly affected for up to four weeks after subcutaneous ivermectin treatment of cattle (0.2 mg·kg -1 ) [70,86,113,114]. Adult females of the sheep blowfly Lucilia cuprina exhibited impaired ovarian development, reduced fecundity and reduced survival when fed continuously on sheep dung collected within 24 hours of oral treatment with ivermectin, whereas adult males showed aberrant mating behaviour [20,21,71,72]. The face fly Musca autumnalis showed a 14-46 day period of reduced larval development [70,96], on the contrary to the stable fly Stomoxys calcitrans where less toxic effects were observed after subcutaneous ivermectin treatment of cattle [90].…”
Section: Concentration Stability and Activity Of Anthelmintics In Thmentioning
confidence: 99%